Stakeholders’ Perceptions on Marine Spatial Planning in Bangladesh: Entwining Strategic Approach - Ashikur, M R; Mahdiuzzaman, M; Rupom, R S; Sakib, Mohammad Nazmus (BIMRAD Journal, 2025)
Marine Spatial Planning (MSP) is a form of comprehensive planning that focuses on the management of marine space to achieve ecological, economic, and social objectives. Such kinds of objectives influence the adoption of the best practices that introduce the blue economy and other coastal and marine resources in the maritime boundaries of Bangladesh. This research was carried out to analyze the opportunities and challenges for the establishment and implementation of MSP in Bangladesh. Also, the study focused on a better strategic approach for adopting MSP in Bangladesh under the current scenario. The questionnaire, opinion survey, and focus group discussions were conducted to collect the data from the maritime professionals, stakeholders, academicians, planners, environmentalists, lawyers, policymakers, and marine/ oceanography students of the different universities. Among the participants, about 65% of respondents responded an independent authority would be good for developing MSP in Bangladesh. From the aftermath, it appeared that stakeholder involvement in the implementation of MSP was rather low due to a lack of adequate research facilities and knowledge. The research also identified insufficient financial support, competent human resources, geospatial data, and lack of coordination among the institutions as challenges to MSP development in Bangladesh. As a consequence of this study’s findings, it has been proposed that strong legal frameworks should be used, existing institutions should be integrated, a dedicated financial budget should be allocated, stakeholders should be involved, and a single database might be developed. Finally, a strategic framework has been suggested for implementing MSP in Bangladesh based on the findings. Besides, the framework presents the notion regarding the way to establish MSP in Bangladesh. BIMRAD Journal VOLUME 5, ISSUE 1, DEC 2024; PP-129-162